TELAAH PENGANDAIAN FILOSOFIS RELASI INTEGRASI IUS (MATERIL) DAN FORMAL (LEGES) DALAM HUKUM, SEPERTI RELASI JIWA DAN RAGA - Fransiskus Saverius Nurdin (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2018)
Material (Ius) is a reality that does not appear in law while Formal (Leges) is a realitythat appears in law. These two elements one form a unite called law, cannot beseparated. The reality of materia and form in law is also identicaly with the integrationof mind and body that exist in human integrity as a person. This study describes therelations between these two realities philosophically way. This research is a legalresearch based on library research and uses a philosophical approach.